Qualitative Study: The Impact of Teamwork on the Effectiveness of Employee Performance at the Langsa City Regional Financial Management Agency - Hutapeya, Rico Marcahaya; Hot Tua Siboro, Ricardo Maruba; Herbert P.A Butar-Butar, Rio; Hasibuan, Zul Henry Awal; Sianturi, Purwanto; Pane, Sri Gustina (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to analyze the impact of teamwork on the effectiveness of employee performance at the Langsa City Regional Financial Management Agency (BPKD). This research uses a qualitative method with data collection techniques in the form of in-depth interviews, observations, and documentation studies. The results of the study show that effective teamwork has a significant influence on improving work efficiency, productivity, and service quality. Factors such as open communication, clear division of roles, and supportive leadership play an important role in building a solid team. Although some challenges such as conflicts and differences in perception between team members arise, these challenges can be managed well through mediation and participatory leadership. Technology has also been shown to help facilitate team communication and collaboration. Overall, the study concludes that good teamwork contributes to more effective employee performance and betterquality public services. These results support team management theories that state that structured collaboration supported by appropriate leadership can increase organizational productivity.